(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This paper examines the impact of digital technologies on taxation and the changing approaches to tax processes in the context of the digitalization of the economy. The aim of the study is to analyze how modern digital tools, such as automation, artificial intelligence, and big data, are transforming traditional methods of taxation, improving the efficiency and transparency of tax systems. The section "Digitalization of Tax Processes" focuses on the implementation of electronic reporting systems and tax platforms that streamline tax procedures for both businesses and governments. It explores contemporary approaches to the creation and use of online systems for tax declaration submission and online tax payment, as well as the use of blockchain technologies to enhance transparency in tax calculations. Special attention is given to new approaches to taxation, such as the use of artificial intelligence and big data analysis for more accurate assessment of tax liabilities, improved tax control, and fraud prevention. The paper analyzes the advantages of digital technologies for taxation, including the increased efficiency of tax collection, reduction of administrative costs, and improvement of interaction between taxpayers and tax authorities. However, the implementation of digital technologies is also associated with a number of challenges, including issues related to privacy and data protection, as well as potential risks of digital inequality, particularly in countries with low levels of digital infrastructure. The paper discusses these issues and suggests possible solutions. In conclusion, the importance of further development of digital technologies in taxation is emphasized, along with opportunities to enhance global tax compliance and improve financial systems at the international level